Kesulitan Belajar Siswa dalam Memahami Materi Hidrokarbon Kelas XI-3 SMA Negeri 1 Palangka Raya Tahun Ajaran 2024/2025 - Damayanti, Rizki Eka Putri; Sidauruk, Suandi; Meiliawati, Ruli (Jurnal Ilmiah Kanderang Tingang, 2025)
This study aims to describe the learning difficulties of students in class XI-3 on the hydrocarbon topic at SMA Negeri 1 Palangka Raya in the 2024/2025 academic year. The study employed a quantitative descriptive approach with 40 students as the sample, selected using purposive sampling technique. The research was conducted using a diagnostic test instrument in the form of matching-type questions. The results of the study showed that the level of student learning difficulties in the hydrocarbon topic in class XI-3 of SMA Negeri 1 Palangka Raya was in the low category, which was 29.77%, or it can be said that 12 out of 40 students in class XI-3 experienced difficulties in learning the hydrocarbon topic.